Plant-Specific AtS40.4 Acts as a Negative Regulator in Abscisic Acid Signaling During Seed Germination and Seedling Growth in Arabidopsis - Shi, Xiao-Pu; Ren, Jing-Jing; Qi, Hao-Dong; Lin, Yi; Wang, Yu-Yi; Li, De-Feng; Kong, Lan-Jing; Wang, Xiu-Ling (Frontiers in Plant Science, 2021)
Abscisic acid (ABA) is an important phytohormone regulating plant growth, development and stress responses. A multitude of key factors implicated in ABA signaling have been identified; however, the regulation network of these factors needs for further information. AtS40.4, a plant-specific DUF584 domain-containing protein, was identified previously as a senescence regulator in Arabidopsis. In this study, our finding showed that AtS40.4 was negatively involved in ABA signaling during seed germination and early seedling growth. AtS40.4 was highly expressed in seeds and seedlings, and the expression level was promoted by ABA. AtS40.4 was localized both in the nucleus and the cytoplasm. Moreover, the subcellular localization pattern of AtS40.4 was affected by ABA. The knockdown mutants of AtS40.4 exhibited an increased sensitivity to ABA, whereas the overexpression of AtS40.4 decreased the ABA response during seed germination and seedling growth of Arabidopsis. Furthermore, AtS40.4 was involved in ABRE-dependent ABA signaling and influenced the expression levels of ABA INSENTIVE (ABI)1-5 and SnRK2.6. Further genetic evidence demonstrated that AtS40.4 functioned upstream of ABI4. These findings support the notion that AtS40.4 is a novel negative regulator of the ABA response network during seed germination and early seedling growth.